Administration of colistin sulfate in endotoxic model at slow and sustained fashion may reverse shock without causing nephrotoxicity in its optimal concentration. (December 2017) - Haque, Anwarul; Ishii, Yoshikazu; Akasaka, Yoshikiyo; Matsumoto, Tetsuya; Tateda, Kazuhiro
Highlights: Colistin sulfate was infused in endotoxic models at a slow and sustained manner. Colistin sulfate infusion rescued shock without causing nephrotoxicity. The study showed a wide therapeutic window of colistin sulfate. Described a promising way to use colistin sulfate without adverse effects. Brought scope to study polymyxin in bacterial infections with a novel approach. Abstract: Objectives: Despite of proven LPS neutralizing activity, intravenous polymyxin use was waned due to experience of associated nephrotoxicity. But, increasing resistance to all available antibiotics has necessitated their resurgence and the prodrug of colistin sulfate (CS), known as colistin-methanesulfonate (CMS), is increasingly used as the only therapeutic option in many infections. Currently available CMS employ very different dose definitions and thus because of complex pharmacokinetics/pharmacodynamics information and short half-life, this drug use remains confusing. We aimed to expose CS in endotoxic shock models by micro-osmotic pump and evaluated its effectiveness. Methods: We used micro-osmotic pumps to deliver either sterile saline or CS at different dosages ranging from 0.25 mg/day to 7 mg/day for consecutive 3 days in LPS (8 mg/kg body weight) induced endotoxic mice and observed their outcome twice daily for a week to determine the survival rate. Serum pro-inflammatory cytokine levels and apoptosis in renal tissues in these models were evaluated. Results: We showed endotoxic shock was reversed and all mice survived with a CS administration at a dosage of 2 mg/day for 3 days, in comparison to survival rate with saline administration (p ≤ 0.0001) in endotoxic models. CS infusion in shock models using micro-osmotic pump ameliorated rising of serum TNF-α, IL-12p70 and IL-6 levels. Nephrotoxicity was evident only with a higher dosage, but not with a lower dosage which was optimum to control endotoxic shock in models. Conclusions: These results highlighted that an optimal dosage of CS effectively improved outcome in endotoxic shock models without causing nephrotoxicity when administered at a slow and sustained manner. And a higher CS dosage administration was nephrotoxic and fatal. Thus this study bought an opportunity to consider future investigations with CS administration in murine Gram-negative bacterial infections in a novel way.